Chronic nodular prurigo: clinical profile and burden. A European cross‐sectional study. (12th May 2020) - Pereira, M.P.; Hoffmann, V.; Weisshaar, E.; Wallengren, J.; Halvorsen, J.A.; Garcovich, S.; Misery, L.; Brenaut, E.; Savk, E.; Potekaev, N.; Lvov, A.; Bobko, S.; et al.
Abstract: Background: Chronic nodular prurigo (CNPG) is a condition characterized by chronic itch, a prolonged scratching behaviour and the presence of pruriginous nodules. A comprehensive understanding of this condition, especially regarding its clinical characteristics and impact on quality of life is still lacking. Objectives: Aim of this pan‐European multicentre cross‐sectional study was to establish the clinical profile of CNPG, including its associated burden. Methods: Fifteen centres from 12 European countries recruited CNPG patients presenting at the centre or using the centres' own databases. Patients were asked to complete a questionnaire in paper or electronic format. Demography, current co‐morbidities, underlying disease, itch intensity, additional sensory symptoms, quality of life, highest burden and emotional experience of itch were assessed. Results: A total of 509 patients (210 male, median age: 64 years [52; 72]) were enrolled. Of these, 406 reported itch and CNPG lesions in the previous 7 days and qualified to complete the whole questionnaire. We recorded moderate to severe worst itch intensity scores in the previous 24 h. Scores were higher in patients with lower educational levels and those coming from Eastern or Southern Europe. Most patients experience itch often or always (71%) and report that their everyday life is negatively affected (53%). Itch intensity was considered to be the most burdensome aspect of the disease by 49% of the patients, followed by the visibility of skin lesions (21%) and bleeding of lesions (21%). The majority of patients was unaware of an underlying condition contributing to CNPG (64%), while psychiatric diseases were the conditions most often mentioned in association with CNPG (19%). Conclusions: This multicentre cross‐sectional study shows that itch is the dominant symptom in CNPG and reveals that the profile of the disease is similar throughout Europe.